Exploring the Immunopathogenesis of Viral Hemorrhagic Fever in Mice with a Humanized Immune System - Schönrich, Günther; Raftery, Martin J. (Frontiers in Immunology, 2017)
Viral hemorrhagic fever (VHF) as a disease entity was first codified in the 1930s by soviet scientists investigating patients suffering from hantavirus infection. The group of hemorrhagic fever viruses (HFVs) has since expanded to include members from at least four different virus families: Arenaviridae, Bunyaviridae, Filoviridae, and Flaviviridae, all enveloped single-stranded RNA viruses. After infection the natural hosts of HFVs do not develop symptoms whereas humans can be severely affected. This observation and other evidence from experimental data suggest that the human immune system plays a crucial role in VHF pathogenesis. For this reason mice with a human immune system, referred to here as humanized mice (humice), are valuable tools that provide insight into disease mechanisms and allow for preclinical testing of novel vaccinations approaches as well as antiviral agents. In this article we review the impact of humice in VHF research.